2022
DOI: 10.3389/fpls.2022.1012231
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key gene networks controlling polysaccharide accumulation in different tissues of Polygonatum cyrtonema Hua by integrating metabolic phenotypes and gene expression profiles

Abstract: Plant polysaccharides, a type of important bioactive compound, are involved in multiple plant defense mechanisms, and in particular polysaccharide-alleviated abiotic stress has been well studied. Polygonatum cyrtonema Hua (P. cyrtonema Hua) is a medicinal and edible perennial plant that is used in traditional Chinese medicine and is rich in polysaccharides. Previous studies suggested that sucrose might act as a precursor for polysaccharide biosynthesis. However, the role of sucrose metabolism and transport in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The Polygonati rhizome , also referred as (Huangjing), not only does it features prominently in the Chinese as a herb, but also widely distribution in the whole world (Chen et al ., 2022). Traditionally, the Polygonatum rhizome has been used as a medicinal resource traditionally, setting it apart from the other parts of the plant of medicine, unlike the rest of the plant (Qi et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Polygonati rhizome , also referred as (Huangjing), not only does it features prominently in the Chinese as a herb, but also widely distribution in the whole world (Chen et al ., 2022). Traditionally, the Polygonatum rhizome has been used as a medicinal resource traditionally, setting it apart from the other parts of the plant of medicine, unlike the rest of the plant (Qi et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, how to improve the bioavailability and biological activity of the plant nutrients contained in this valuable herbal resource in it is also a problem that researchers continue to explore at both home and abroad. Currently, the study of bioactive components within P. cyrtonema Hua mainly concentrated on the polysaccharides, with a specific focus on their potential antitumor activity and underlying mechanisms of biological activity action (Huang et al ., 2020; Chen et al ., 2022). However, another substance, such as phenolic, has been concluded in the scope of active ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, INV plays a role in breaking down sucrose into fructose and glucose in plants. It is involved in cell osmotic regulation and the accumulation of sugar in storage organs, providing substrates for the subsequent synthesis of polysaccharides ( Chen et al, 2022 ). HXK facilitates glucose phosphorylation in plant cells, while fructose undergoes phosphorylation by fructose kinase prior to metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted to demonstrate that carbohydrates were the primary components of Polygonatum's aerial parts. Several studies compared the carbohydrate composition of the stems, leaves, and flowers, and it was found that the flowers had the highest polysaccharide content, and the stems had the highest content of fructose and glucose [7]. In addition, the seeds contained a large amount of starch, with a content proportion of about 60.9-65.2% of the total; moreover, the soluble sugar content in the seeds of PC was as high as 28.4% [8].…”
Section: Introductionmentioning
confidence: 99%